Comparative Transcriptomics of Fat Bodies between Symbiotic and Quasi-Aposymbiotic Adult Females of Blattella germanica with Emphasis on the Metabolic Integration with Its Endosymbiont Blattabacterium and Its Immune System - Silva, Francisco J.; Domínguez-Santos, Rebeca; Latorre, Amparo; García-Ferris, Carlos (International journal of molecular sciences, 2024)
We explored the metabolic integration of Blattella germanica and its obligate endosymbiont Blattabacterium cuenoti by the transcriptomic analysis of the fat body of quasi-aposymbiotic cockroaches, where the endosymbionts were almost entirely removed with rifampicin. Fat bodies from quasi-aposymbiotic insects displayed large differences in gene expression compared to controls. In quasi-aposymbionts, the metabolism of phenylalanine and tyrosine involved in cuticle sclerotization and pigmentation increased drastically to compensate for the deficiency in the biosynthesis of these amino acids by the endosymbionts. On the other hand, the uricolytic pathway and the biosynthesis of uric acid were severely decreased, probably because the reduced population of endosymbionts was unable to metabolize urea to ammonia. Metabolite transporters that could be involved in the endosymbiosis process were identified. Immune system and antimicrobial peptide (AMP) gene expression was also reduced in quasi-aposymbionts, genes encoding peptidoglycan-recognition proteins, which may provide clues for the maintenance of the symbiotic relationship, as well as three AMP genes whose involvement in the symbiotic relationship will require additional analysis. Finally, a search for AMP-like factors that could be involved in controlling the endosymbiont identified two orphan genes encoding proteins smaller than 200 amino acids underexpressed in quasi-aposymbionts, suggesting a role in the host–endosymbiont relationship.